1987
DOI: 10.1002/1097-0142(19871101)60:9<2355::aid-cncr2820600940>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Familial colon cancer in the Tel-Aviv area and the influence of ethnic origin

Abstract: The family history of colon cancer was investigated in 38,823 individuals (2,129 families) who comprised a control and an oncology patient series from Tel-Aviv and nearby areas. A significant increased risk for colon cancer was observed among first-degree relatives of colon cancer patients when compared to controls. When the patient sample was divided into two groups based on country and continent of birth--European (Ashkenazim) and other (nonAshkenazim)--the relatives of the nonAshkenazi subjects showed a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

1992
1992
2004
2004

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 14 publications
(1 reference statement)
0
14
0
2
Order By: Relevance
“…A further limitation is the lack of information on family history. We do know from a previous study, that familial CRC was more commonly found in the non-Ashkenazi CRC patients [4]. So, this cannot explain the higher risk for CRC in the European-Americanborn Jews.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…A further limitation is the lack of information on family history. We do know from a previous study, that familial CRC was more commonly found in the non-Ashkenazi CRC patients [4]. So, this cannot explain the higher risk for CRC in the European-Americanborn Jews.…”
Section: Discussionmentioning
confidence: 83%
“…They include the occurrence of low penetrance susceptibility mutations, uncommon and unrecognized dominant mutations and especially diet and lifestyle [4,5,[14][15][16][17]. The converse findings in Israeli born are, again, speculative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rozen et al [42] investigated the family history of colon cancer in 38,823 individuals (2,129 families) as part of a case-control patient series from Tel-Aviv, Israel, and surrounding locations. There was a significant increased risk for CRC among first-degree relatives of patients affected with CRC compared to controls.…”
Section: Familial Crc In Israelmentioning
confidence: 99%
“…. .set the stage for laboratory-oriented, epidemiologic studies, which might then enable us to extract the crucial components of genetic-environmental interaction in colon carcinogenesis through focusing attention on groups that are distinguished by high, familial clustering of cancer [46][47][48][49][50]'' (cited by Rozen et al [42]). …”
Section: Familial Crc In Israelmentioning
confidence: 99%